Solution to the Master Equation for Nondegenerate Parametric Amplification with Thermal Reservoir (Journal of Atomic and Molecular Sciences, 2011)
By using Lie dynamical algebra representation theory, we have solved the master equation for the nondegenerate parametric amplifier model in a thermal reservoir. Applying a series of transformations, we show that the master equation has multiple commuted SU(1,1) Lie algebra structures. The explicit solution to the master equation has been obtained.